2014
DOI: 10.1001/jamaneurol.2014.290
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation of Parkinson Disease Severity and18F-DTBZ Positron Emission Tomography

Abstract: IMPORTANCE Currently, diagnosis of Parkinson disease is mainly based on clinical criteria characterized by motor symptoms including bradykinesia, rigidity, resting tremor, and postural instability. Reliable in vivo biomarkers to monitor disease severity and reflect the underlying dopaminergic degeneration are important for future disease-modifying therapy in Parkinson disease. OBJECTIVES To use [ 18 F]9-fluoropropyl-(+)-dihydrotetrabenazine (18 F-DTBZ; [ 18 F]AV-133) positron emission tomography (PET) to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 49 publications
(67 reference statements)
7
58
0
Order By: Relevance
“…These findings are consistent with recent in vivo and postmortem findings suggesting that the primary degeneration in PD occurs at the level of the striatal terminals, followed subsequently by cell loss in the SN (34,35). These data would suggest that at the early stage of the disease, a consistent proportion of nigral cells are still viable and could be a suitable target for therapeutic strategies aimed at preserving surviving neurons, to delay the progression of the disease.…”
Section: Dat Binding In Early-pd Patientssupporting
confidence: 91%
“…These findings are consistent with recent in vivo and postmortem findings suggesting that the primary degeneration in PD occurs at the level of the striatal terminals, followed subsequently by cell loss in the SN (34,35). These data would suggest that at the early stage of the disease, a consistent proportion of nigral cells are still viable and could be a suitable target for therapeutic strategies aimed at preserving surviving neurons, to delay the progression of the disease.…”
Section: Dat Binding In Early-pd Patientssupporting
confidence: 91%
“…Parkinson's disease [2,3,22]. In our experiment, we firstly determined the transient equilibrium of 18 F-FP-(+)-DTBZ in rat brain with a dynamic brain distribution study.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of VMAT2 function are associated with many neurodegenerative or neuropsychic disorders. In the past decades, imaging VMAT2 with positron emission tomography (PET) and 18 F-FP-(+)-DTBZ or 11 C-(+)-DTBZ, radiolabeled ligands specific to VMAT2, has demonstrated valuable potentiality for investigating VMAT2 related disorders, such as Parkinson's disease [2][3][4][5], cocaine addiction [6][7][8] and amphetamine abuse [9,10], both in animals and in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The caudate is less affected than the anterior putamen and the anterior putamen less than the posterior putamen. The levels of 18 F-DOPA, DAT binding, and 11 C-DTBZ uptake in the striatum correlate inversely with the clinical disease severity [47][48][49]. Fluorine-18 DTBZ PET images demonstrated that the reduction of VMAT2 availability was obviously correlated with the severity of disease in patients with PD.…”
Section: Clinical Pet Studies and Review Of The Literature In Pdmentioning
confidence: 96%